2020
DOI: 10.1371/journal.pmed.1003359
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed treatment of uncomplicated P. falciparum malaria on progression to severe malaria: A systematic review and a pooled multicentre individual-patient meta-analysis

Abstract: The impact of delayed treatment of uncomplicated P. falciparum malaria on progression to severe malaria: A systematic review and a pooled multicentre individual-patient meta-analysis. PLoS Med 17(10): e1003359.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 71 publications
2
64
0
Order By: Relevance
“…Severe symptoms and the choice or referral to attend primary, secondary or tertiary health care may confound these results. Evidence from clinical studies may reflect this, showing longer delays to treatment than reported here [ 9 , 21 - 23 ]. A more robust assessment of the impact of introducing CHWs on treatment delays would include a comparison of delays in a location before and after deployment of CHWs.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Severe symptoms and the choice or referral to attend primary, secondary or tertiary health care may confound these results. Evidence from clinical studies may reflect this, showing longer delays to treatment than reported here [ 9 , 21 - 23 ]. A more robust assessment of the impact of introducing CHWs on treatment delays would include a comparison of delays in a location before and after deployment of CHWs.…”
Section: Discussionmentioning
confidence: 64%
“…Whilst we can assess evidence of coverage, access and equity outcomes, we do not evaluate the quality of care or downstream health outcomes which are beyond the scope of this analysis. Improved access and reduced delays should lead to improved health outcomes [ 9 , 21 , 23 ] although confounding factors such as quality of care, referral efficiency, treatment seeking behaviour and public/private preferences are also important.…”
Section: Discussionmentioning
confidence: 99%
“…Doctors could deduce the pathogens for patients judged by where they came from, without hours waiting for laboratory testing results for pathogens, giving the possibility of rapid access for treatment. A review con rmed that rapid access for treatment reduced risk of severe disease 24,25 . From our study, most cases came from Democratic Republic of the Congo(DRC), patients from DRC infected by almost all kinds of plasmodium.…”
Section: Clinical Implications For Geographical and Pathogens Distributionsmentioning
confidence: 99%
“…The WHO recommends that treatment for malaria should occur within 24 hours of the onset of malaria symptoms to prevent the advancement of infection [2,5,11]. A recent systematic review on the impact of delaying in seeking malaria treatment indicates that the risk of severe malaria for patients seeking care more than 24 hours was higher than those seeking care less than 24 hours (odds ratio : 1.33, 95% CI: 1.07-1.64) [12]. Moreover, studies on various settings among Asia communities indicated that patients sought care for malaria at health facilities on average at least two days after the onset of symptoms [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%